2012
DOI: 10.1111/j.1476-5381.2012.01991.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelets increase survival of adenocarcinoma cells challenged with anticancer drugs: mechanisms and implications for chemoresistance

Abstract: BACKGROUND AND PURPOSECancer cells grow without the restraints of feedback control mechanisms, leading to increased cancer cell survival. The treatment of cancer is often complicated by the lack of response to chemotherapy leading to chemoresistance and persistent survival of tumour cells. In this work we studied the role of platelets in chemotherapy-induced cancer cell death and survival. EXPERIMENTAL APPROACHHuman adenocarcinoma cells, colonic (Caco-2) and ovarian (59 M) cells, were incubated with 5-fluorour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 54 publications
1
80
0
Order By: Relevance
“…Patients whose pre-treatment biopsy specimens contained platelets surrounding tumor cells at a rate >10% of the total number of tumor cells showed significant residual cancer cells in surgical specimens following chemotherapy. Recent reports have demonstrated that human platelets increase cancer cell survival, proliferation, and chemoresistance to 5-fluorouracil and paclitaxel in colon and ovarian cancer in vivo (27). Moreover, chemoresistance could be induced by platelets throughout EMT (28), PAI-1-mediated anti-apoptotic pathways, direct protection, or immunosuppression mediated by downregulation of NKG2-D (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Patients whose pre-treatment biopsy specimens contained platelets surrounding tumor cells at a rate >10% of the total number of tumor cells showed significant residual cancer cells in surgical specimens following chemotherapy. Recent reports have demonstrated that human platelets increase cancer cell survival, proliferation, and chemoresistance to 5-fluorouracil and paclitaxel in colon and ovarian cancer in vivo (27). Moreover, chemoresistance could be induced by platelets throughout EMT (28), PAI-1-mediated anti-apoptotic pathways, direct protection, or immunosuppression mediated by downregulation of NKG2-D (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Platelets seem to be of special importance for metastasis, since thrombocytosis is frequently observed in patients with metastatic cancers [58] . Platelets facilitate invasion of cancer cells, intra-and extravasation of CTCs (by secreting lysophosphatidic acid) [59,60] , protect them from various host attacks, such as immune assaults [61,62] , apoptosis [63,64] and shear stress [57,65,66] . Importantly, platelets may also contribute to EMT of CTCs and more efficient metastases formation [67] .…”
Section: Staying Mesenchymal -Cooperation With Other Cellsmentioning
confidence: 99%
“…However, they are also involved in many non-hemostatic functions, including tissue repair [1] , inflammation [2], lymphatic development, and angiogenesis [3]. Platelets also boost cancer metastasis and cell proliferation by pericellular adhesion and signal transduction [4][5][6]. Such pleiotropic effects are possible due to the numerous molecules released from activated platelets.…”
Section: Introductionmentioning
confidence: 99%